Epidemiology and Clinical Characteristics of Respiratory Syncytial Virus Infection among Children with Acute Respiratory Illness in Kathmandu, Nepal - Shrestha, Ram Krishna; Shrestha, Sanjeet Kumar; Upadhyay, Bishnu Prasad; Ghimire, Prakash; Banjara, Megha Raj (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory tract infections in young children, particularly in low- and middle-income countries. Data on RSV epidemiology and clinical characteristics in Nepal remain limited.Method: A hospital-based cross-sectional study was conducted from March to August 2025 among 122 children presenting with acute respiratory illness at a tertiary children’s hospital in Kathmandu. Nasopharyngeal swabs were tested using real-time PCR for RSV detection and subtyping :RSV-A and RSV-B. Demographic and clinical data were analyzed using descriptive statistics and inferential tests, including Fisher’s exact test and Mann–Whitney U test.Result: RSV was detected in 19.7% (24/122) of cases—nearly one in five children—with a predominance among males (66.7%). RSV-A was the dominant subtype (75%), followed by RSV-B (25%). Infants constituted the majority of cases (54.2%). CT values demonstrated significantly higher viral loads in children under 12 months (p = 0.02), with a moderate positive correlation between age and Ct value (r = 0.52, p = 0.01), indicating decreasing viral load with increasing age. Although RSV-B showed relatively higher viral loads than RSV-A, the difference was not statistically significant (p = 0.49). Clinical features, including fever, cough, wheezing, and rhinorrhea, were comparable across subtypes, with no statistically significant differences (p > 0.05).Conclusion: RSV was detected in nearly one-fifth of children with acute respiratory illness, predominantly affecting infants. RSV-A was the predominant subtype. Clinical features were similar between RSV-A and RSV-B infections. These findings highlight the substantial burden of RSV in young children in Nepal and underscore the need for enhanced surveillance and preventive strategies.